2005
DOI: 10.1111/j.1365-2648.2005.03448.x
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy: concept analysis

Abstract: An analysis of the concept of health literacy enhances nurses' ability to assess more accurately their clients' levels of health literacy, thus identifying those at risk for misunderstanding health care instructions, shame associated with inadequate reading skills, and inability to adhere to health care recommendations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
195
1
16

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 241 publications
(226 citation statements)
references
References 25 publications
3
195
1
16
Order By: Relevance
“…[3,4,6,16,17] Functional literacy skills consist of two major parts: obtaining and understanding basic health information. The lower right box lists a number of methods that one should incorporate in helping individuals make appropriate health decisions such as 1) using plain/primary language, 2) incorporating a teach-back method, and 3) avoiding jargons.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…[3,4,6,16,17] Functional literacy skills consist of two major parts: obtaining and understanding basic health information. The lower right box lists a number of methods that one should incorporate in helping individuals make appropriate health decisions such as 1) using plain/primary language, 2) incorporating a teach-back method, and 3) avoiding jargons.…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…10 These studies 10,[23][24][25][26][27][28][29][30][31][33][34][35][36]46 also emphasized that inadequate FHL is highly prevalent among the elderly, perhaps reflecting a weakness in the health system, in which older individuals are required to play a more active role in the management of their own health. Strategies of health literacy could be given more attention by healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…4,8 Studies have reported that FHL is a relatively new concept in the area of health promotion. 9,10 It is also considered an emerging field in the areas of education and health promotion. 4 FHL has attracted the interest of researchers, health professionals and public policy creators, due to its complex, multi-dimensional and interdisciplinary nature, as well as the impact that poor literacy can exert on an individual, their family, the community and the health system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of health literacy depends on various factors, such as socio-economic status, gender, ethnic affiliation and ethnicity, the severity of the disease, previous experiences related to health, occupation and other [2][3][4][5][6]. General literacy and the level of education are also among the important factors of health literacy [1,[7][8][9].…”
mentioning
confidence: 99%